Analysis of Thermal Degradation in the Annealing Process of Colored Parts Built by Extrusion-Based 3D Printing - Castro Vera, Kleber Leonardo; Santana, Leonardo; Lino Alves, Jorge (International Journal of Engineering and Management Sciences, 2020)
With the ever-increasing request of light materials, poly lactic (acid) PLA, have got much in consideration. Low-cost PLA materials have risen its use. Those possess some benefits but nevertheless insufficient mechanical strength. The printed PLA objects have a stumbling block for practical applications. Thus, annealing is an interested alternative to make 3D printed objects strong. This thermal treatment can significantly develop investigational studies and offer technical data. Hence the purpose of this paper is study and discuss how to increase the flexural strength through annealing process. Geometry distortions and color degradation will be analyzed. Differential Scanning Calorimetry, Taguchi Method (TM) and variance (ANOVA) were applied as part of the design experiments and analysis. Twenty-seven printed specimens were tested and factors as temperature, time and color were selected.